A novel collaborative requirement prioritization approach to handle priority vagueness and inter-relationships - Ankita Gupta; Chetna Gupta (Journal of King Saud University: Computer and Information Sciences, 2022)
One of the challenging tasks of requirement engineering is to choose which among the set of requirements are more advantageous than others and ought to be viewed as first for execution. Years of research has established it is vital to capture, analyze and prioritize requirements, which to a great extent relies on acknowledgment acceptance of stakeholder’s requirements, concerns and criteria’s. Proposed method provides interactive support for eliciting stakeholders and developer’s initial ranking decision in collaborative manner. Intuitionistic Fuzzy Approach (IFS) is used to support stakeholders view; whereas analysis of inter relationships, requirement slicing and backtracking are used to support developers view using weighted page rank algorithm. Finally a ranking is generated in a collaborative manner to support requirement prioritization. The feasibility of the approach is illustrated through an experimental proof of concept by comparing results of proposed approach with state of art, Analytic Hierarchy Process (AHP) and Interactive Genetic Algorithm (IGA) prioritization techniques. Results of experimentation conclude that presented approach is capable of producing accurate and comparable results by handling technical constraints of dependency, tradeoffs of collaboration and scope of inclusion of initial multi-criteria preferences expressed as priority values to support reliability and robustness to errors.